2018
DOI: 10.1016/j.appet.2018.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Consumers' evaluation of imported organic food products: The role of geographical distance

Abstract: Country-of-origin (COO) effects and consumer evaluation of organic food products are rarely studied in combination. The aim of this study was therefore to investigate organic consumers' preferences for imported organic food products from different origins and the underlying reasons for these preferences, including how consumers' COO preferences depend on the geographical distance to the COO. We employed a multi-method, qualitative approach consisting of in-store interviews (N = 255) and focus groups (six, N = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 43 publications
3
32
0
Order By: Relevance
“…All factors being equal, freshness will be sacrificed for price -convenience will be sacrificed for price -and features like universal access, customer convenience, and even positive aspects of store service will be sacrificed for price. However, it has been shown that consumers usually prefer local food or food originated from a geographically closer country [16], our study raises the attention to the significant effect of price; hence our results are not surprising. It would be reasonable to expect that economic drivers would be a high priority, if not the highest priority, for a consumer.…”
Section: Discussionsupporting
confidence: 46%
“…All factors being equal, freshness will be sacrificed for price -convenience will be sacrificed for price -and features like universal access, customer convenience, and even positive aspects of store service will be sacrificed for price. However, it has been shown that consumers usually prefer local food or food originated from a geographically closer country [16], our study raises the attention to the significant effect of price; hence our results are not surprising. It would be reasonable to expect that economic drivers would be a high priority, if not the highest priority, for a consumer.…”
Section: Discussionsupporting
confidence: 46%
“…This contrasts with evidence from European markets where typically domestic origin is more valuable to consumers than organic certification per se (de‐Magistris & Gracia, 2014) but echoes the findings for China where localness is a far less valuable attribute (Wu et al., 2014). European consumers tend to trust food from their own country far more than imports (Pedersen et al., 2018) but this may not be the case for emerging economies.…”
Section: Discussionmentioning
confidence: 99%
“…In South Africa, the demand of OGPs is increasingly becoming more critical as consumer attitudes and preferences influence the direction of food retailers’ strategies [1,3,12]. This market shift is due to consumers’ interests for safe alternatives, exclusively, OGPs [13,14]. Currently, OGPs are perceived as healthy by most consumers as these are made up of natural elements and mostly preferred compared to conventionally grown products.…”
Section: Introductionmentioning
confidence: 99%